Polanyi and Schumpeter: Transitional processes via societal spheres. Issue 6 (2nd November 2022) - Hager, Theresa; Heck, Ines; Rath, Johanna
Abstract: We examine parallels and differences, intersections and complementarities in the notions of societal transition by Karl Polanyi and Joseph A. Schumpeter. Considering their intellectual heritage, methodology and scope, we propose a three-sphere framework to analyse their theories and study the interdependencies within capitalism. The three spheres essential to both thinkers are the political, the socio-cultural and the economic: the latter dominates the others in capitalist societies. The resulting rationalisation (Schumpeter) and commodification (Polanyi) distort the socio-cultural sphere and transcend towards the political sphere which undermines democracy. Applying our framework, we identify similar transitional mechanisms but derive different implications for society.